Cellulose structure and lignin distribution in normal and compression wood of the Maidenhair tree (Ginkgo biloba L.). Issue 4 (April 2015) - Andersson, Seppo; Wang, Yurong; Pönni, Raili; Hänninen, Tuomas; Mononen, Marko; Ren, Haiqing; Serimaa, Ritva; Saranpää, Pekka
Abstract We studied in detail the mean microfibril angle and the width of cellulose crystals from the pith to the bark of a 15‐year‐old Maidenhair tree (Ginkgo biloba L.). The orientation of cellulose microfibrils with respect to the cell axis and the width and length of cellulose crystallites were determined using X‐ray diffraction. Raman microscopy was used to compare the lignin distribution in the cell wall of normal/opposite and compression wood, which was found near the pith. Ginkgo biloba showed a relatively large mean microfibril angle, varying between 19° and 39° in the S2 layer, and the average width of cellulose crystallites was 3.1–3.2 nm. Mild compression wood without any intercellular spaces or helical cavities was observed near the pith. Slit‐like bordered pit openings and a heavily lignified S2L layer confirmed the presence of compression wood. Ginkgo biloba showed typical features present in the juvenile wood of conifers. The microfibril angle remained large over the 14 annual rings. The entire stem disc, with a diameter of 18 cm, was considered to consist of juvenile wood. The properties of juvenile and compression wood as well as the cellulose orientation and crystalline width indicate that the wood formation of G. biloba is similar to that of modern conifers.